Antiproliferative quillaic acid and gypsogenin saponins from Saponaria officinalis L. roots. (May 2015) - Lu, Yuping; Van, Dang; Deibert, Leah; Bishop, Greg; Balsevich, John
Graphical abstract: Extraction of soapwort roots led to isolation of 14 purified quillaic acid and gypsogenin bisdesmosidic saponins. Structures were determined mainly on the basis of extensive NMR experiments. The compounds were evaluated for hemolytic and antiproliferative activities. Highlights: Fourteen bisdesmosidic saponins were isolated from root extract and their structures elucidated. Method for shifting obfuscating water peak in 1 H NMR spectrum developed. Hemolytic activities determined. Growth inhibitory activities in two human cancer cell lines determined. Abstract: Nine quillaic acid and five gypsogenin bisdesmosides were isolated from roots of Saponaria officinalis L. (Caryophyllaceae). Seven of the quillaic acid saponins possessed a 3- O - β -d -galactopyranosyl-(1 → 2)-[ β -d -xylopyranosyl-(1 → 3)]- β -d -glucuronopyranosyl unit, but differed from each other in oligosaccharide units linked to the C-28 ester. The five gypsogenin saponins isolated from the roots all possessed the 3- O - β -d -galactopyranosyl-(1 → 2)-[ β -d -xylopyranosyl-(1 → 3)]- β -d -glucuronopyranosyl unit, with their oligosaccharide units linked to the C-28 ester differing. Structures were elucidated by extensive 1D and 2D NMR spectroscopy and mass spectrometry. The saponins were evaluated for growth inhibitory activity in two human cancer cell lines and hemolytic activity in sheep red blood cells.